Hepatitis C virus detection and management after implementation of universal screening in pregnancyAJOG Global Reports at a Glance - Sarah Boudova, MD, PhD; Danielle M. Tholey, MD; Elizabeth Ferries-Rowe, MD (Elsevier, 2024)
BACKGROUND: Accurately identifying cases of hepatitis C virus has important medical and public health consequences. In the setting of rising hepatitis C virus prevalence and highly effective treatment with direct-acting antivirals, the Society for Maternal-Fetal Medicine guidelines recently changed to recommend universal screening for hepatitis C virus during pregnancy. However, there is little data on the influence of this policy change on case identification and management. OBJECTIVE: We aimed to examine the influence of universal hepatitis C virus screening on our patient population. Our primary objective was to determine if there was a difference in the detected hepatitis C virus prevalence after the policy change. Our secondary objectives were to determine which factors were associated with a positive test for hepatitis C virus and to examine postpartum management of pregnant patients living with hepatitis C virus, including the (1) gastroenterology referral rate, (2) treatment rate, (3) infantile hepatitis C virus screening rate, and (4) factors associated with being referred for treatment. STUDY DESIGN: We conducted a single-center, retrospective cohort study of deliveries that occurred before (July 2018-June 2020) and after (July 2020-December 2021) the implementation of universal hepatitis C virus screening. Information on hepatitis C virus and HIV status, if patients were screened for hepatitis C virus, history of intravenous drug use, and basic demographic information were abstracted from the electronic medical records. A subset of patients was administered a questionnaire regarding hepatitis C virus risk factors. For all patients who tested positive for hepatitis C virus, information on if they were referred for treatment in the postpartum period and if their infant was screened for hepatitis C virus were abstracted from the electronic medical records. RESULTS: A total of 8973 deliveries occurred during this study period. A total of 71 (0.79%) patients had a detectable viral load. With implementation of universal screening, hepatitis C virus screening rates increased from 5.78% to 77.25% of deliveries (P<.01). The hepatitis C virus prevalence rates before and after universal screening was implemented were 0.78% and 0.81%, respectively (P=.88). There were significant demographic shifts in our pregnant population over this time period, including a reduction in intravenous drug use. A subset of 958 patients completed a hepatitis C virus risk factor questionnaire, in addition to undergoing universal hepatitis C virus screening. Ten patients screened positive with universal screening; only 8 of these individuals would have been identified with risk-based screening. Among the patients with a detectable viral load, 67.61% were referred for treatment and 18.75% were treated. A multivariate logistic regression model indicated that intravenous drug use was associated with significantly decreased odds of being referred for treatment (odds ratio, 0.14; 95% confidence interval, 0.04-0.59; P=.01). At the time of our evaluation, 52 infants were at least 18 months old and thus eligible for hepatitis C virus screening. Among these infants, 8 (15.38%) were screened for hepatitis C virus, and all were negative. CONCLUSION: Following the practice shift, we saw a significant increase in hepatitis C virus screening during pregnancy. However, postpartum treatment and infant screening remained low. Intravenous drug use was associated with a decreased likelihood of being referred for treatment. Pregnancy represents a unique time for hepatitis C virus case identification, although better linkage to care is needed to increase postpartum treatment.